Interference of Arabidopsis N-Acetylglucosamine-1-P Uridylyltransferase Expression Impairs Protein N-Glycosylation and Induces ABA-Mediated Salt Sensitivity During Seed Germination and Early Seedling Development - Chen, Ya-Huei; Shen, Hwei-Ling; Chou, Shu-Jen; Sato, Yasushi; Cheng, Wan-Hsing (Frontiers in Plant Science, 2022)
N-acetylglucosamine (GlcNAc) is the fundamental amino sugar moiety that is essential for protein glycosylation. UDP-GlcNAc, an active form of GlcNAc, is synthesized through the hexosamine biosynthetic pathway (HBP). Arabidopsis N-acetylglucosamine-1-P uridylyltransferases (GlcNAc1pUTs), encoded by GlcNA.UTs, catalyze the last step in the HBP pathway, but their biochemical and molecular functions are less clear. In this study, the GlcNA.UT1 expression was knocked down by the double-stranded RNA interference (dsRNAi) in the glcna.ut2 null mutant background. The RNAi transgenic plants, which are referred to as iU1, displayed the reduced UDP-GlcNAc biosynthesis, altered protein N-glycosylation and induced an unfolded protein response under salt-stressed conditions. Moreover, the iU1 transgenic plants displayed sterility and salt hypersensitivity, including delay of both seed germination and early seedling establishment, which is associated with the induction of ABA biosynthesis and signaling. These salt hypersensitive phenotypes can be rescued by exogenous fluridone, an inhibitor of ABA biosynthesis, and by introducing an ABA-deficient mutant allele nced3 into iU1 transgenic plants. Transcriptomic analyses further supported the upregulated genes that were involved in ABA biosynthesis and signaling networks, and response to salt stress in iU1 plants. Collectively, these data indicated that GlcNAc1pUTs are essential for UDP-GlcNAc biosynthesis, protein N-glycosylation, fertility, and the response of plants to salt stress through ABA signaling pathways during seed germination and early seedling development.